The relation between socioeconomic status and invasive haemodynamics at evaluation for advanced heart failure - Johan E. Larsson; Søren Lund Kristensen; Tania Deis; Peder E. Warming; Morten Schou; Lars Køber; Søren Boesgaard; Kasper Rossing; Finn Gustafsson (ESC Heart Failure)
Abstract Aims Socioeconomic deprivation is a risk marker for worse prognosis in patients with heart failure (HF), and a potential barrier to referral for advanced HF evaluation. The relationship between socioeconomic status (SES) and invasive haemodynamics in patients undergoing evaluation for advanced HF therapies is unknown. Methods We combined a consecutive clinical registry of patients evaluated for advanced HF with patient‐level data on SES (household income, education, workforce status, cohabitant status and distance from home to tertiary HF centre) derived from nationwide registries. Using this information, the cohort was divided into groups of low‐, medium‐ and high degree of socioeconomic deprivation. The associations between SES and invasive haemodynamics were explored with multiple linear regression adjusted for age and sex. Results A total of 631 patients were included. The median age was 53 years, and 23% were women. Patients in the highest income quartile versus the lowest (Q4 vs. Q1) were older (median age 57 vs. 50 years) and more often male (83% vs. 67%), both P < 0.001. Increasing household income (per 100 000 Danish kroner,1 EUR = 7.4 DKK) was associated with lower pulmonary capillary wedge pressure (PCWP) [−0.18 mmHg, 95% confidence interval (CI) −0.36 to −0.01, P = 0.036] but not significantly associated with central venous pressure (CVP) (−0.07 mmHg, 95% CI −0.21 to 0.06, P = 0.27), cardiac index (−0.004 L/min/m2, 95% CI −0.02 to 0.01, P = 0.60), or pulmonary vascular resistance (PVR) (−0.003 Wood units, 95% CI −0.37 to 0.16, P = 0.84). Comparing the most deprived with the least deprived group, adjusted mean PVR was higher (0.35 Wood units, 95% CI 0.02 to 0.68, P = 0.04), but PCWP (0.66 mmHg, 95% CI −1.49 to 2.82, P = 0.55), CVP (−0.26 mmHg, 95% CI −1.76 to 1.24, P = 0.73) and cardiac index (−0.03 L/min/m2, 95% CI −0.22 to 0.17, P = 0.78) were similar. Conclusions Most haemodynamic measurements were similar across layers of SES. Nevertheless, there were some indications of worse haemodynamics in patients with lower household income or a high accumulated burden of socioeconomic deprivation. Particular attention may be warranted in socioeconomically deprived patients to ensure timely referral for advanced HF evaluation.